A fuzzy analytic network process based approach to transportation-mode selection between Turkey and Germany: A case study - Tuzkaya, Umut R.; Onut, Semih (ELSEVIER SCIENCE INC, 2008)
A case study examining the different modes for transportation of freight by a Turkish logistics-service provider company is presented herein. A number of conflicting qualitative and quantitative criteria exist for evaluating alternative modes of transport. Qualitative criteria are often accompanied by ambiguity and vagueness. To cope with ambiguity and vagueness problem, the fuzzy analytic network process (ANP) method has been used. A large number of detailed criteria that interact with each other have been evaluated and synthesized to obtain the most suitable transportation mode. This evaluation has been carried out by a group of decision makers coming from different management levels and functional areas in the sector of logistics and from the service company with intent to provide a more accurate and mutually acceptable solution. Furthermore, the model used here has been validated by comparing the results obtained with the current preferences of the company. (c) 2008 Elsevier Inc. All rights reserved.
Keywords: analytic network process (ANP); fuzzy sets; transportation-mode selection; OPTIMIZATION; SYSTEM; ANP; DESIGN; Computer Science